Fillier. North River. Photograph of people around kitchen table with birthday cake. (1990)
A photograph of 4 people, 2 men and 2 women, sitting around a kitchen table cutting into a birthday cake. Left to right: James Snow, Clara Snow (Efford), Marjorie (Snow) FIllier. circa 1990s.